Juridical Analysis of Constitutional Court Decision Number 135/PUU-XXII/2024: The Shift of the Constitutional Court's Role as a Positive Legislator in Indonesia's Electoral System - Diki Prayitno; Ahmad Suryono (Empat Sembilan Publisher, 2026)
This research aims to analyze the role of the Constitutional Court as a positive legislator in the Constitutional Court Decision Number 135/PUU-XXII/2024. The decision caused debate because the Constitutional Court not only tested the constitutionality of the norm, but also formulated a new norm regarding the separation of the implementation of National Elections and Regional Elections with a minimum interval of 2 (two) years and a maximum of 2 (two) years and 6 (six) months. This research uses a normative legal research method with a legislative approach and a case approach. The legal materials used include the 1945 Constitution of the Republic of Indonesia, Law Number 7 of 2017 concerning General Elections, Law Number 8 of 2015, and the Constitutional Court Decision Number 135/PUU-XXII/2024. The research results show that the Constitutional Court in the a quo decision has played a role as a positive legislator through a conditional unconstitutional decision (conditionally unconstitutional) which not only cancels the norm, but also provides the formulation of new norms as a guideline for the implementation of elections in Indonesia. The action was carried out to fill the legal vacuum, improve the quality of democracy, strengthen the sovereignty of the people, maintain the effectiveness of the party system, and create legal certainty in the implementation of elections. Thus, the Constitutional Court Decision Number 135/PUU-XXII/2024 shows a shift in the role of the Constitutional Court from negative legislators to positive legislators, because the Court not only acts as a law examiner of the constitution, but also plays an active role in the formation of binding legal norms